Efeito da hidrotermica em abacate ‘Hass’ sobre a capacidade antioxidante, compostos fenólicos e coloração - Tremocoldi, Maria Augusta [UNESP]; Daiuto, Erica Regina [UNESP]; Alencar, Severino Matias de; Vieites, Rogério Lopes [UNESP] (Univ Estadual Londrina, 2014)
This study aimed to determine the antioxidant activity, total phenolic compounds and color in avocado 'Hass' hydrothermally treated. The fruits were hydrothermally treated at 45 degrees C for 5, 10, 15 and 20 min. After treatment, fruit were stored at room temperature (21 +/- 1 degrees C and 70 +/- 5% relative humidity) and cold (10 degrees C +/- 1 and 90 +/- 5% relative humidity). The fruits were analyzed for their antioxidant capacity by DPPH method and phenolic compounds at 0, 3, 9 and 12 days. The fruits color was measured at 0, 3, 6, 9, 12 and 15 days. The control fruits had higher antioxidant capacity and content of phenolic compounds during the storage period, compared to the fruits hydrothermally treated. The hydrothermally treatment altered the behavior as for the maintenance of the antioxidant activity in relation to the fruits control. In spite of superior values of antioxidant activity for the fruits maintained at 21 +/- 1 degrees C and 70 +/- 5% relative humidity, those refrigerated presented better aspect for commercialization. The refrigerated fruits presented better aspect for commercialization in relation to the maintained under room temperature. The brightness, color a * and b * values decreased with the storage days. Values color superiors were observed for the fruits control and those maintained under refrigeration. As it increased the irradiation dose reduced the fruits antioxidant activity and coloration.
Effect of hydrothermally Hass avocado about antioxidant capacity, total phenolic content and coloration
Keywords: Persea Americana Mill; refrigeration; postharvest